'Caplan's Syndrome' – revisited and lessons learned. Issue 5 (1st October 2005) - Caplan, Louis R.
Abstract : In the mid 1980s, I had just taken up the Neurology Chair at Tufts University in Boston. Dr Ted Munsat the previous Neurology chairman said to me that the Tufts' neurology residents would probably not know about Caplan's syndrome. I thought hard to myself – Caplan's syndrome. Was he referring to the top-of–the basilar syndrome that I had published in 1980 (Caplan 1980). I asked him if that was what he meant by Caplan's syndrome. No, he said. I then thought of the other two recent syndromic descriptions- lateral tegmental haemorrhages (Caplan & Goodwin 1982) and cervical vertebral artery dissections (Caplan et al. 1985). These two areas, as well as the top-of the basilar, were about posterior circulation syndromes, well known to be a special interest of mine. I have already discussed awakening of interest in posterior circulation strokes in a previous paper in Practical Neurology (Caplan 2004). 'No', Munsat